Effect of low magnetic field treatment on spectra of radiative recombination centers in indium phosphide structures - Red’ko, R. R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
We present the results of investigations of the effect caused by low magnetic
field treatment on InP single crystals impurity-defect composition. This effect was found
when studying the radiative recombination (luminescence) spectra in the 0.6-2.5 µm
range at 77 K. The static magnet with B = 0.44 T was used as a source of magnetic field.
We studied samples of two groups: porous InP crystals and epitaxial layers grown on
porous substrate. The crystals of both groups were not specially doped. It has been
obtained that treatment even for 0.02 min resulted in considerable changes in
luminescence spectra. The luminescence intensities after treatment increase at first, but
later behavior is nonmonotonic: next treatment can result in decrease or increase a value
of intensities of both observed bands. It should be noted that the luminescence intensities
of epitaxial layers, perhaps, changed as well as concentration of nonradiative centers
changed. But for porous indium phosphide, these features were not observed.